Fatores influenciadores para adoção de energia solar fotovoltaica no Brasil - Stolf, Eduardo José (Universidade do Vale do Rio dos Sinos, 2018)
With recent water crises in Brazil, consumers of residential electricity may seek other technologies for supply, such as solar photovoltaic energy. In addition, the economic and environmental issue makes increasing interest in so-called green energy generation technologies. In this sense, photovoltaic solar energy is considered one of the most promising energy technologies by experts worldwide, but the adoption of photovoltaic solar energy in Brazil still represents a very small share of the national energy source. Therefore, in this study, we explored influencing factors that have a significant effect on the intentions of using this new technology. The orientation factors for innovation, environmental awareness, quality of the system, perceived trust, knowledge, to determine the attitude and intention to use solar photovoltaic energy were related. In this context, this study aims to propose and test a theoretical model to analyze some influencing factors for the adoption of photovoltaic solar energy. To achieve this goal, data were collected through a survey of 420 respondents. Afterwards, the results were analyzed through a structural equation modeling method to the proposed research model. This research indicated that three positive factors, which include the orientation towards innovation, environmental awareness and the quality of the system, contribute significantly to determine the attitude of the public in relation to photovoltaic solar energy technology. The intention to use technology was also determined by three positive variables (attitude, perceived confidence and knowledge). With this, all the hypotheses proposed in this conceptual model were confirmed. Based on empirical findings from this study, the implications and suggestions are presented and discussed in this paper.
Keywords: Energia solar; Fotovoltaica; Adoção; Solar energy; Photovoltaic; Adoption; ACCNPQ::Ciências Sociais Aplicadas::Administração